PARAMETERS INDICATING DEVELOPMENT OF HYPERTENSION IN THREE-YEAR FOLLOW-UP STUDY OF SUBJECTS WITH HIGH NORMAL BLOOD PRESSURE. (June 2022) - Kalos, Theodoros; Dimitriadis, Kyriakos; Konstantinidis, Dimitrios; Siafi, Eirini; Kariori, Maria; Kakouri, Niki; Manta, Eleni; Tatakis, Fotis; Polyzos, Dimitrios; Drogkaris, Sotiris; Zammanis, Ioannis; Fragoulis, Christos; et al.
Abstract : Objective: Assess the relation of hypertensive response to exercise (HRE) in subjects with high normal blood pressure (BP) while sympathetic overactivity assessed by muscle sympathetic nerve activity (MSNA) and arterial stiffening are linked with development of hypertension (HTN). Design and method: 100 consecutive subjects with high normal BP [systolic BP = 130–139mmHg and/or diastolic BP = 85–89mmHg], underwent a negative for ischemia treadmill exercise test (Bruce protocol). Arterial stiffness was evaluated using carotid-femoral pulse wave velocity (PWV). Sympathetic drive was assessed by MSNA. Follow-up was scheduled every 6 months for 3 consecutive years, where BP measurements were assessed in office and with ambulatory BP monitoring (ABPM). All participants offered lifestyle advice. Endpoint was development of HTN either with OffBP or ABPM. We divided into Group I those who developed HTN and Group II without HTN. Results: From 100 subjects (54 ± 8 years, 42 males, baseline OffBP: 132/82 mmHg, 24-hour BP: 122/76 mmHg) 40 developed HTN (Group I) and 50 developed HRE (BP> or = 210mmHg in men and > or = 190mmHg in women). Group I vs II had higher HRE (75%vs13%, p = 0.026) with intermediate stage intervals of 3 min (160vs147mmHg, p = 0.068) and 6 min (181vs164mmHg, p = 0.035). The SBP/MET-slope [(peakSBP—restingSBP)/(peakMET-1)] in Group I was increased in all stages till peak exercise (stage1: 6.25vs4.25, stage2: 7.6vs5.3, peak: 7.22vs5.1, p = 0.035). Their exercise capacity was reduced (10vs11.5METs) as their maximum exercise heart rate (154vs164, p = 0.001). They demonstrated higher levels of PWV (8.35vs7.5m/sec, p = 0.043) and MSNA levels (37vs31 bursts, p = 0.04), while did not differ regarding their metabolic profile at the follow-up. Echocardiographicly LVMI did not differ, but LVEDD (47vs45 mm, p = 0.02), E/A ratio of mitral valve inflow (0.92vs1.05, p = 0.034) and left atrium diameter (3.8vs3.6 mm p < 0.1) were statistically significant. At their initial ECG had shorter P-wave duration (101.3vs93.2, p = 0.013) and QRS duration (93.4vs85.7, p = 0.006). In ABPM they demonstrated higher night systolic BP (116vs112mmHg, p < 0.04). Conclusions: In subjects with high normal BP, MSNA identifies a state of increased sympathetic overdrive, PWV demonstrates arterial stiffening and exercise testing proves its prognostic value as a hypertension predictor screening tool acknowledging a state of increased systemic vascular resistance.